Kerahasiaan Teks Basis Data MySQL Menggunakan Algoritma Elgamal - Atmaja, Niko Surya (Jurnal Sistim Informasi dan Teknologi, 2019)
The common method used to secure a MySQL database is in access control. The technique is the use of a password. To better secure the data sent cryptographic techniques need to be done. This study uses the Elgamal method in conducting cryptography. The results of this study generate MySQL databases in random form during safer delivery and can only be accessed by parties who have a password. So this research can further improve MySQL data security